Merancang Data Mining untuk Mendukung Strategi Cross-Selling - Handijono, Ardijan; Suhatman, Zaldy (Program Studi Teknik Informatika Universitas Pamulang, 2023)
Up-Selling and Cross-Selling are part of a CRM (Customer Relationship Management) strategy. Up-Selling is a way to encourage consumers to buy a better product that has a higher value than what has been purchased. Meanwhile, Cross-Selling is a method to offer complementary or additional products. In large outlets with product items that can reach thousands, it is not easy to be able to identify related products automatically and quickly. To be able to provide a solution to this problem, a literature study will be carried out in several journals regarding CRM, Data Mining and Call-Centers. In the Cross-Selling strategy, Data Mining can be used to identify a product that is related to any product by analyzing the customer's shopping basket in the transaction history, this technique is also known as MBA (Market Basket Analysis). The results of Data Mining are product/service recommendations that have a strong correlation with several other products that customers usually buy. By adding Call-Center technology and CTI (Computer Telephony Integration) recommendations from Data Mining can be followed up by Telemarketing Agents to offer products/services directly to Customers.